Between family and friends: The choice of corporate ownership structure - Castillo Ponce, Ramón A. (Estudios Económicos de El Colegio de México, 2007)
The document presents an analysis, developed under the framework of conflict theory, which models the choice of ownership structure as the result of a power struggle between the owner of a firm and potential shareholders. The theoretical model suggests that, when the system that protects property rights is inefficient, the choice of keeping the ownership of the firm within the family represents the strategy that provides the owner the highest value when going public.